The potential risk of using historic claims to set bundled payment prices: the case of physical therapy after lower extremity joint replacement - Sander Steenhuis; Geeske Hofstra; France Portrait; Fatima Amankour; Xander Koolman; Eric van der Hijden (BMC, 2022)
Abstract Background One of the most significant challenges of implementing a multi-provider bundled payment contract is to determine an appropriate, casemix-adjusted total bundle price. The most frequently used approach is to leverage historic care utilization based on claims data. However, those claims data may not accurately reflect appropriate care (e.g. due to supplier induced demand and moral hazard effects). This study aims to examine variation in claims-based costs of post-discharge primary care physical therapy (PT) utilization after total knee and hip arthroplasties (TKA/THA) for osteoarthritis patients. Methods This retrospective cohort study used multilevel linear regression analyses to predict the factors that explain the variation in the utilization of post-discharge PT after TKA or THA for osteoarthritis patients, based on the historic (2015-2018) claims data of a large Dutch health insurer. The factors were structured as predisposing, enabling or need factors according to the behavioral model of Andersen. Results The 15,309 TKA and 14,325 THA patients included in this study received an average of 20.7 (SD 11.3) and 16.7 (SD 10.1) post-discharge PT sessions, respectively. Results showed that the enabling factor 'presence of supplementary insurance' was the strongest predictor for post-discharge PT utilization in both groups (TKA: β = 7.46, SE = 0.498, p-value< 0.001; THA: β = 5.72, SE = 0.515, p-value< 0.001). There were also some statistically significant predisposing and need factors, but their effects were smaller. Conclusions This study shows that if enabling factors (such as supplementary insurance coverage or co-payments) are not taken into account in risk-adjustment of the bundle price, they may cause historic claims-based pricing methods to over- or underestimate appropriate post-discharge primary care PT use, which would result in a bundle price that is either too high or too low. Not adjusting bundle prices for all relevant casemix factors is a risk because it can hamper the successful implementation of bundled payment contracts and the desired changes in care delivery it aims to support.